Integration techniques in digital video production - Ivanova, Yoana (Yearbook Telecommunications, 2024)
The aim of this paper is to present basic digital integration techniques that are applied in the television and film industry to create a final product that meets modern quality criteria. Emphasis is placed on applied methods of creating video content for various purposes, as well as on the main components of the technological equipment of a professional television studio. The scientific-applied contribution is expressed in a comparative analysis of software products for video processing (Adobe Premiere Pro and Openshot Video Editor), which is supported by step-by-step algorithms for the implementation of basic integration techniques in digital video production. The conclusions made regarding the characteristics, possibilities and advantages of the selected products are intended to support the interns in the process of their assimilation and effective use for the realization of creative projects.